2021
DOI: 10.3390/antiox10060864
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Quality Control by Plasma Glutathione Status

Abstract: Timely centrifugation of blood for plasma preparation is a key step to ensure high plasma quality for analytics. Delays during preparation can significantly influence readouts of key clinical parameters. However, in a routine clinical environment, a strictly controlled timeline is often not feasible. The next best approach is to control for sample preparation delays by a marker that provides a readout of the time-dependent degradation of the sample. In this study, we explored the usefulness of glutathione stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This preference for plasma may be attributed to some of its advantages over serum, such as a larger volume, no clotting time delay and a lower risk of haemolysis or the breakdown of erythrocytes ( Uges, 1988 ). In fact, contamination from degrading/leaking erythrocytes can artificially increase GSH and GSSG levels in both plasma and serum, given that these cells contain approximately two orders of magnitude higher glutathione than the liquid portion of blood ( Tomin et al, 2021 ). A linear increase in both plasma GSH and GSSG levels was demonstrated for blood left at room temperature over a three hour observation period, with significant increases becoming evident as early as one hour post-collection ( Tomin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This preference for plasma may be attributed to some of its advantages over serum, such as a larger volume, no clotting time delay and a lower risk of haemolysis or the breakdown of erythrocytes ( Uges, 1988 ). In fact, contamination from degrading/leaking erythrocytes can artificially increase GSH and GSSG levels in both plasma and serum, given that these cells contain approximately two orders of magnitude higher glutathione than the liquid portion of blood ( Tomin et al, 2021 ). A linear increase in both plasma GSH and GSSG levels was demonstrated for blood left at room temperature over a three hour observation period, with significant increases becoming evident as early as one hour post-collection ( Tomin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, contamination from degrading/leaking erythrocytes can artificially increase GSH and GSSG levels in both plasma and serum, given that these cells contain approximately two orders of magnitude higher glutathione than the liquid portion of blood ( Tomin et al, 2021 ). A linear increase in both plasma GSH and GSSG levels was demonstrated for blood left at room temperature over a three hour observation period, with significant increases becoming evident as early as one hour post-collection ( Tomin et al, 2021 ). Ten of 16 (63%) blood studies in our review reported the time to processing of plasma or serum, and all performed this step within 20 min of blood draw ( Supplementary Table S3 ), thereby minimizing glutathione contamination from erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GSH quantification in whole blood is challenged by the complexity of the blood matrix as well as the rapid deterioration of the sample, including enzymatic- and non-enzymatic GSH oxidation [ 12 , 13 , 14 , 15 , 16 ]. Furthermore, GSH levels were proposed as a surrogate for assessing the time-dependent degradation of blood samples prior to plasma extraction, as even minor leakages of GSH from erythrocytes lead to an increase in plasmatic GSH levels [ 17 ]. Whilst GSH concentrations in blood plasma ranging between 2 and 20 μM have been reported in the literature, in whole blood, they are notably higher (mM range), as over 95% of GSH is located inside the erythrocytes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%